Development of a laminar burning velocity empirical correlation for combustion of iso-octane/ethanol blends in air. (1st January 2022) - Sekularac, N.; Fang, X.H.; Shankar, V.; Baker, S.J.; Leach, F.C.P.; Davy, M.H.
Abstract: This study presents the first demonstration of Marshall and Hinton's empirical correlation for laminar burning velocity (LBV) applied to iso-octane/ethanol blends. The "Oxford" correlation is first validated for neat iso-octane and ethanol combustion against the outputs of three different chemical kinetics mechanisms and experimental data from the literature. The effects of three different mixing rules, simple energy fraction, modified Le Châtelier, and modified version of the more complex mixing law of Hirasawa, on the predicted LBVs of iso-octane/ethanol blends are evaluated. The modified Le Châtelier mixing law is used with the Oxford correlation to predict blend LBVs at various temperature and pressure conditions. The results are validated against previously unpublished data for iso-octane/ethanol binary fuels at elevated temperature and pressure (up to 10 bar) both from this group, and from the earlier experimental studies of Varea et al. (CORIA) and Broustail et al. (PRISME). The Oxford correlation is shown to perform well across a wide range of temperature and pressure conditions (respectively 298–640 K and 1–10 bar) for the single component fuels. Used in conjunction with a modified Le Châtelier mixing law, the LBVs predicted by the correlation provide an excellent match to the available experimental data across the full range of ethanol concentrations examined (25, 50, and 75% v/v). Highlights: An empirical laminar burning velocity correlation is validated for isooctane/ethanol blends. Novel experimental data for iso-octane/ethanol binary fuels at elevated conditions. Modified Le Châtelier rule gave good results for all unburned temperature and pressure conditions.